Application of the Hungarian Method for Assigning Workers to Ciptaland Development - Wosvo Aritonang; Nelly Astuti Hasibuan; Rivalri Kristianto Hondro (STMIK Budi Darma, 2020)
Assignment of workers is something that is needed by the company. But in reality the company is difficult to place its employees in each allocation. However, with the development of existing technology, this can be minimized by calculating the cost of each work and each allocation by utilizing existing data and extraction to produce new knowledge. The application of operational research techniques using the Hungarian method and tested using a system or application as a decision tree to assign some decent workers to be placed on jobs within the company. Therefore the author took the initiative to make a thesis entitled